Mapping oil spill environmental sensitivity in cardoso island state park and surroundings areas, São Paulo, Brazil - Wieczorek, Arthur; Dias-Brito, Dimas; Carlos, Joao; Milanelli, Carvalho (Elsevier B.V., 2007)
This study presents an environmental oil spill sensitivity map of Cardoso Island State Park, located in São Paulo state, Brazil, including some of its surrounding areas. This map was designed following the procedures determined by the Brazilian Federal Environment Organ (Ministry of the Environment), which separates coastal habitats in different littoral sensitivity indexes (LSI) to oil spills. We have also analysed some seasonal variations in morphologic and textural parameters at the local marine beaches that could affect their sensitivity, having found that they are more sensitive during summer due to a wider foreshore zone during these periods. Local most sensitive habitats are estuarine mangroves (LSI 10) and estuarine mud banks (LSI 9). Marine beaches were ranked LSI 3, and littoral rocky shores were subdivided in exposed flat rocky shores (LSI 1), boulder rocky shores (LSI 6) and sheltered rocky shores (LSI 8). Due to the elevated sensitivity of an estuarine system in the area, we considered necessary the installation of an Environmental Emergency Centre and the design of an emergency plan for the region in case of an accident resulting in oil spills within its vicinities. (C) 2007 Elsevier Ltd. All rights reserved.